Some Preliminary Observations on Root-Knot Nematodes of Vegetable Crops in Tripoli Region of Libyan Jamahiriya - KHAN, M. WAJID; DABAJ, KHALIFA H. (The Libyan Journal of Agriculture, 2023)
Preliminary observations were made during the survey of root-knot nematode problems on vegetable crops grown in the coastal belt from Al-Khoms to Janzoor. Many of the field plots, glasshouses and plastic tunnels of vegetables in the area were infested with root-knot nematodes. Vegetable crops of tomato, potato, cucumber, eggplant, pepper, broad-bean, bean, cauliflower, onion, and radish were infected to a varying extent. Severity of the disease was more in indoor cultivations. Infections on cucumber, tomato, pepper and eggplant were more widespread than potato, broadbean. bean, cauliflower, onion and radish. Meloidogvne incognita and M.javanica were identified as the species responsible for damage on these vegetable crops. M. incognita was found on cucumber, broad-bean, pepper, and tomato; while M.javanica on eggplant, bean, cauliflower, onion, potato, radish and broad-bean. These two species appear to be widely distributed on vegetables in the areas surveyed. The occurrence of root-knot nematode on cucumber, cauliflower, onion and radish are new records for Jamahiriya.